2020
DOI: 10.1371/journal.pone.0231423
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of the accessible interface of biopsy-derived canine intestinal organoids to study epithelial-luminal interactions

Abstract: Recent advances in canine intestinal organoids have expanded the option for building a better in vitro model to investigate translational science of intestinal physiology and pathology between humans and animals. However, the three-dimensional geometry and the enclosed lumen of canine intestinal organoids considerably hinder the access to the apical side of epithelium for investigating the nutrient and drug absorption, host-microbiome crosstalk, and pharmaceutical toxicity testing. Thus, the creation of a pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 61 publications
6
47
0
Order By: Relevance
“…Furthermore, the enclosed lumen in an organoid body considerably hampers access to the lumen, by which the co-culture with gut microbiome or the simulation of drug administration is extremely challenging. Thus, this limitation led to the innovation of an “opened” version of an organoid, where the recreation of a mucosal tissue interface of intestinal organoids has been emerged [ 6 , 48 , 49 ]. On top of the previous reports [ 20 , 50 ], we propose an advanced 3D convoluted microdevice that can manipulate multiaxial deformations and independently controlled fluid hydrodynamics in the mucosal interface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enclosed lumen in an organoid body considerably hampers access to the lumen, by which the co-culture with gut microbiome or the simulation of drug administration is extremely challenging. Thus, this limitation led to the innovation of an “opened” version of an organoid, where the recreation of a mucosal tissue interface of intestinal organoids has been emerged [ 6 , 48 , 49 ]. On top of the previous reports [ 20 , 50 ], we propose an advanced 3D convoluted microdevice that can manipulate multiaxial deformations and independently controlled fluid hydrodynamics in the mucosal interface.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed a positive effect of IBD treatment using PRBs and GAGs in addition to the hydrolyzed diet alone. Mechanistic effects of glycerophospholipids or TGs could be tested in our recently established intestinal cell models to better recapitulate canine intestine (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived xenografts (PDX) is an approach whereby patient tumor fragments are implanted into immunocompromised mice to generate tumors that recapitulate genomic and phenotypical features of patient's original tumor 30,31 . PDX have value in both better understanding tumor biology and evaluating the efficacy of FDA-approved anticancer therapies or novel targeted treatments 37 . Although PDX models present an exciting opportunity for improving predictive value of preclinical studies, there are several hurdles to their translation into the clinic.…”
Section: Preclinical 2d and Patient-derived Xenograft Models Bring Vamentioning
confidence: 99%
“…In addition, xenografted urine-derived organoids were able to cause tumorigenesis in immunodeficient mice demonstrating their ability to maintain oncogenic properties ex vivo. Characterization of organoids can be done through an array of cellular and molecular techniques including immunohistochemistry, RNA-Seq, proteomics, and others 37,38,39 . Leveraging our expertise in the culture and maintenance of canine organoids, our consortium has successfully cultured MIBC organoids from urinary samples of 6/6 human patients ( Fig.…”
Section: Patient-derived Tumor Organoids: a Preclinical Platform For mentioning
confidence: 99%
See 1 more Smart Citation